Intellectual Capital Efficiency from the Lens of Audit Committee Attributes - Waseem, Fareeha; Abbas , Syeda Fizza; Butt, Muskan Atif (Audit and Accounting Review, 2022)
The purpose of this research is to find out the association between audit committee traits and intellectual capital efficiency in the context of Pakistan. For this purpose, this study employs a sample of 28 banks covering a duration of 10 years (2010-2020). Furthermore, this study employs audit committee attributes as an independent variable, while the dependent variable is the efficiency of intellectual capital, which is measured by using the value-added intellectual coefficient (VAIC) approach. As the audit committee aids in strengthening the internal control systems by overseeing the top management decision-making process, thus, it improves the overall effectiveness of organizations. Preluding to the control system process, the results of this study are justified by revealing a significantly positive impact of audit attributes on banks’ intellectual capital efficiency. Therefore, this research illustrates the insights of intellectual capital efficiency with audit committee attributes as a major component, which would be significant for managers in making decisions regarding audit committee composition to increase intellectual capital in the developing nations.